Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1034/j.1399-0020.2000.290501.x
|View full text |Cite
|
Sign up to set email alerts
|

A short-term study in sheep with the Groningen temporomandibular joint prosthesis

Abstract: As part of the pre-clinical testing process of a newly developed temporomandibular joint (TMJ) prosthesis, animal experiments were performed. In 14 sheep, the right TMJ was replaced by the developed TMJ prosthesis. The prosthesis consisted of a skull part, a mandibular part and an intervening polyethylene disc. In the first series (6 sheep), three designs were tested, differing in the applied metal (stainless steel or titanium) and in the fitting method of the skull part (a fitting member or bone cement). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The study results showed that 3 staggered bone screws can provide optimal implant stability and bone stress and strain distributions in a TMJ condylar prosthesis . This finding supported the study findings of by van Loon et al, who performed experiments in sheep and found that a TMJ condylar prosthesis could be firmly fixated using three screws (van Loon et al, 2000a). In this study, the maximum relative micromotion values between the TMJ condylar prosthesis and bone for the six clenching tasks were all less than 28 mm, which is the maximum relative micromotion that can be tolerated for bone ingrowth into the implant surface (Pilliar et al, 1986).…”
Section: Discussionsupporting
confidence: 93%
“…The study results showed that 3 staggered bone screws can provide optimal implant stability and bone stress and strain distributions in a TMJ condylar prosthesis . This finding supported the study findings of by van Loon et al, who performed experiments in sheep and found that a TMJ condylar prosthesis could be firmly fixated using three screws (van Loon et al, 2000a). In this study, the maximum relative micromotion values between the TMJ condylar prosthesis and bone for the six clenching tasks were all less than 28 mm, which is the maximum relative micromotion that can be tolerated for bone ingrowth into the implant surface (Pilliar et al, 1986).…”
Section: Discussionsupporting
confidence: 93%
“…Sheep have bone remodeling patterns similar to those of humans [21], with at least equal chewing forces. The TMJ undergoes adaptive changes even when chewing causes only minor displacement of the condylar head, while articular degenerative changes may develop earlier in adults because of their poor aptitude for subchondral bone remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 This lack of testing is a significant shortcoming, as mechanical properties and wear resistance play a pivotal role in determining the long term outcomes of TJR and, therefore, the need for revision or replacement surgery. 2,7 As far as the authors are aware of, Van Loon et al 12,13 are the only group to publish their in vitro TMJ TJR wear results, prior to commercial release of their prosthesis. They designed a wear testing machine, which simulated the articulation of the mandibular head against the ultra-high molecular weight polyethylene (UHMWPE) disc, while the implant was submerged in bovine fetal calf serum, diluted with distilled water.…”
mentioning
confidence: 99%